(x+5)(x+7)=8

Simple and best practice solution for (x+5)(x+7)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+5)(x+7)=8 equation:

Simplifying
(x + 5)(x + 7) = 8
Reorder the terms:
(5 + x)(x + 7) = 8
Reorder the terms:
(5 + x)(7 + x) = 8
Multiply (5 + x) * (7 + x)
(5(7 + x) + x(7 + x)) = 8
((7 * 5 + x * 5) + x(7 + x)) = 8
((35 + 5x) + x(7 + x)) = 8
(35 + 5x + (7 * x + x * x)) = 8
(35 + 5x + (7x + x2)) = 8
Combine like terms: 5x + 7x = 12x
(35 + 12x + x2) = 8
Solving
35 + 12x + x2 = 8
Solving for variable 'x'.
Reorder the terms:
35 + -8 + 12x + x2 = 8 + -8
Combine like terms: 35 + -8 = 27
27 + 12x + x2 = 8 + -8
Combine like terms: 8 + -8 = 0
27 + 12x + x2 = 0
Factor a trinomial.
(9 + x)(3 + x) = 0
Subproblem 1Set the factor '(9 + x)' equal to zero and attempt to solve:
Simplifying
9 + x = 0
Solving
9 + x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-9' to each side of the equation.
9 + -9 + x = 0 + -9
Combine like terms: 9 + -9 = 0
0 + x = 0 + -9
x = 0 + -9
Combine like terms: 0 + -9 = -9
x = -9
Simplifying
x = -9
Subproblem 2Set the factor '(3 + x)' equal to zero and attempt to solve:
Simplifying
3 + x = 0
Solving
3 + x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-3' to each side of the equation.
3 + -3 + x = 0 + -3
Combine like terms: 3 + -3 = 0
0 + x = 0 + -3
x = 0 + -3
Combine like terms: 0 + -3 = -3
x = -3
Simplifying
x = -3Solutionx = {-9, -3}`